Phenotypic characterization of regulatory CD4+CD25+ T cells in rats. - Stephens, L; Barclay, N; Mason, D (2004)
CD25 has become widely used as a marker for a subset of regulatory CD4(+) T cells present in the thymus and periphery of mice, rats and humans. However, CD25 is also expressed on conventionally activated T cells that are not regulatory and not all peripheral regulatory T cells express CD25. The identification of a stable and unique marker for regulatory T cells would therefore be valuable. This study provides a detailed account of the phenotype of CD4(+)CD25(+) regulatory T cells in rats. In the thymus, CD4(+)CD8(-)CD25(+) cells were found to have a more mature phenotype than the corresponding CD4(+)CD8(-)CD25(-) cells with respect to expression of Thy1 (CD90), CD53 and CD44, suggesting that CD25 expression, and perhaps commitment to regulatory function, might be a late event in thymocyte development. CD4(+)CD25(+) cells in both the thymus and periphery were found to have enriched and heterogeneous expression of activation markers such as OX40 (CD134) and OX48 (an antibody determined in this study to be specific for CD86). CD4(+)CD25(+) T cells were also found to have enriched expression of CD80, at both the mRNA and protein level. However, functional studies in vitro and in vivo showed that neither OX40 or CD86 were useful markers for the further subdivision of regulatory T cells. Our studies indicate that, at present, CD25 remains the most useful marker to enrich for regulatory CD4(+) T cells in rats and no further subdivision of the regulatory component of CD4(+)CD25(-)CD45RC(low) T cells has yet been achieved.